LAO TZU’S NON-ACTION THOUGHT AND ITS VALUE - Vo Van Dung (International Journal of Psychosocial Rehabilitation, 2020)
Lao Tzu’s non-action thought (Wu wei) was born and developed in the historical period of Spring and Autumn - Warring States in which the society was dramatically turbulent. At that time, most ancient Chinese philosophical thought aimed at transforming society from being chaotic to being flourishing through the improvement of human awareness. Hence, Lao Tzu was not an exception when he gave the doctrine of Tao which consists of systematic views and a dialectical ideology with the laws of equilibrium, repetition and non-action theory. Also, the theory of non-action aspired to convert the current society into a peaceful and prosperous one. Up to now, his “non-action” thought still has certain positive value. However, when researching into Lao Tzu’s “non-action” thought, we find that many scientists have had incomprehensive views towards his thought. Through this article, we hope to put them in the right place.